2008
DOI: 10.1021/jp076632q
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Photoemission of Ultrathin Film PTCDA Morphologies on Ag(111)

Abstract: Morphology-and layer-dependent electronic structure and dynamics at the PTCDA/Ag(111) interface have been studied with angle-resolved two-photon photoemission. In Stranski-Krastanov growth modes, the exposed wetting layer inhibited the evolution of the vacuum level and valence band to bulk values. For layer-by-layer growth, we observed the transition of electron structure from monolayer to bulk values within eight monolayers. Effective masses and lifetimes of the conduction band and the n = 1 image potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…Energetic ordering of the states was determined by changing the wavelength of the probe pulse and measuring the change in photoelectron energy. The increased binding of the n=1 image potential state at the 6T/Ag(111) interface compared to the clean silver binding energy of -.77 eV is consistent with other organic semiconductor metal interfaces that have a high electron affinity (> 2 eV) 30,63,64 . Increased coverage had a negligible affect on the workfunction or binding energy of the n=1 peak.…”
Section: Resultssupporting
confidence: 79%
“…Energetic ordering of the states was determined by changing the wavelength of the probe pulse and measuring the change in photoelectron energy. The increased binding of the n=1 image potential state at the 6T/Ag(111) interface compared to the clean silver binding energy of -.77 eV is consistent with other organic semiconductor metal interfaces that have a high electron affinity (> 2 eV) 30,63,64 . Increased coverage had a negligible affect on the workfunction or binding energy of the n=1 peak.…”
Section: Resultssupporting
confidence: 79%
“…10,11 It originates from the Shockley state of the Ag(111) surface which is upshifted from below the metallic Fermi level by as much as 0.7 eV. The initially partially occupied state becomes unoccupied and approaches the conduction band of the organic semiconductor.…”
mentioning
confidence: 99%
“…They reported that its effective mass depends on specific preparation conditions and interpreted this in terms of a varying overlap of the LUMO þ 1 level of neighboring molecules [7].…”
mentioning
confidence: 99%